Medicating the mind: a Kantian analysis of overprescribing psychoactive drugs - Manninen, B. A. (Journal of medical ethics, 2006)
Psychoactive drugs are being prescribed to millions of Americans at an increasing rate. In many cases these drugs are necessary in order to overcome debilitating emotional problems. Yet in other instances, these drugs are used to supplant, not supplement, interpersonal therapy. The process of overcoming emotional obstacles by introspection and the attainment of self knowledge is gradually being eroded via the gratuitous use of psychoactive medication in order to rapidly attain a release from the common problems that life inevitably presents us with. In this paper, I argue that Kant’s formula of humanity, which maintains that persons ought never to treat others or themselves soley as a means to an end, proscribes this. Moreover, Kant argues that we have an imperfect duty of self development, and I argue that we fail to adhere to such a duty whenever we seek to evade the process of introspection and self knowledge in favour of the expedient results that drugs may provide us with as we attempt to overcome the emotional hurdles in our lives.